Teaching and Learning Crystal structures through Virtual Reality based systems. (October 2021) - Kumar, Vishawash; Gulati, Sahil; Deka, Bhargab; Sarma, Himangshu
Abstract: Teaching and learning through Virtual Reality(VR) is an emerging technology in the last few years. In this article, the development and use of a VR based teaching–learning system for crystal structures are discussed. The VR system is designed as a lab environment where a user can do experiments related to crystal structures. The VR system is designed in Unity, 1 and Oculus Rift S 2 is used as a VR headset. Currently, the system consists of three phases; in the first phase user can visualize the crystal lattice structures, wherein the second one a user can visualize the light interaction with the crystal lattice structure using a virtual torch ray. The third phase is the X-ray Diffraction (XRD) experiment. In this phase, users can perform the XRD experiment in the lab environment by taking a random crystal from a crystal dispenser machine and placing it in the X-ray machine which identifies the chosen crystalline material and analyses the unit cell. The incident ray colour changes when there is a peak found in the crystal for a better understanding of the user. There is also an interactive display where users can increase/decrease the angles of the radiation and also lock and unlock the experiment to view the diffraction plot for the crystal structure. In many cases, it was found that XRD and the crystal structure is available in the course syllabus but there are no experiments to enhance their learning. Therefore an experiment with 39 participants was performed where the maximum participants are new to crystallography. The study was conducted in two phases; in the first phase, participants are asked to watch video tutorials of the topic followed by questionnaires; in the second phase participants are asked to do the VR based experiment and followed by questionnaires related to overall study and experiment. From the analysis of the study we found that everyone found VR based teaching methods are better than traditional book/video studies. Study results give an average score of 56.74% in comparison to VR based learning approach with an average score of 93.81%. Participants who took part in the experiment found the experience interactive and motivating and found it helpful to learn elusive concepts, which can be learned when simulated. For example, one participant wrote: "The VR experience was surreal and was easy to control. Lucid user experience. Got a view of XRD like never seen before".